Monitoring Corrosion in Oxide and Chloride Environments Using Ultrasonic Guided Waves - Sharma, S.; Mukherjee, Abhijit (American Society of Civil Engineers (ASCE), 2011)
Ultrasonic guided waves have been used for monitoring progression of rebar corrosion in concrete in chloride and oxide environments. The effect of rates of corrosion in the two environments on the ultrasonic signals is reported. Surface- and core-seeking guided wave modes were used to monitor beams undergoing accelerated impressed current corrosion in the presence (chloride corrosion) and absence of chlorides (oxide corrosion). Effective combination of guided wave modes could relate to the differences in corrosion mechanisms and rates in the two environments. Ultrasonic test results correlated well with that of the destructive tests